Investigation of antimicrobial resistance in pigeons (Columba livia domestica) using indicator bacteria - ASLANTAŞ, Ö; GÖVCE, N. (Journal of the Hellenic Veterinary Medical Society, 2020)
The aim of this study was to determine the prevalence of antibiotic resistance as well as presence of resistance-associated genes in Escherichia coli and Enterococcus spp. strains isolated from pigeons. One hundred and fifty cloacal swabs were collected from apparently healthy pigeons in Hatay, Turkey, between March 2014 and June 2014. Antimicrobial susceptibilities of the isolates were tested with disc diffusion method, and resistance genes were investigated by polymerase chain reaction (PCR). E. coli were isolated from 94.7% (142) of the examined cloacal swab samples. E. coli isolates revealed higher resistance rates to tetracycline (51.4%) and ampicillin (50%), followed by nalidixic acid (19.7%), streptomycin (12.7%), amoxycillin-clavulanic acid (15.5%), trimethoprim-sulfamethoxazole (10.6%), cephalothin (7.0%), ciprofloxacin (6.3%), kanamycin (4.9%), gentamicin (4.2%), tobramycin (4.2%), ceftazidime (4.2%), cefotaxime (4.2%), chloramphenicol (2.8%), aztreonam (2.8%), and cefoxitin (0.7%), respectively. Twentyeight (%19.7) E. coli isolates were susceptible to all tested antimicrobials. A total of 136 (90.7%) Enterococcus spp. were isolated and species distribution of the isolates was determined by species-specific PCR. The isolates were identified as 64 (47.1%) E. hirae, 17 (12.5%) E. faecium, 8 (5.9%) E. faecalis, 4 (2.9%) E. columbea, and 2 (1.5%) E. durans. The rest of the isolates (30.1%) were identified as Enterococcus spp. with the used primers. Enterococcus spp. were resistant to tetracycline (67.6%), erythromycin (23.5%), rifampicin (17.6%), chloramphenicol (6.6%) and ciprofloxacin (5.9%). By contrast, 38 (27.9%) Enterococcus spp. were sensitive to all tested antimicrobials. The data obtained in the study showed that pigeons were carriers of antimicrobial resistant E. coli and Enterococcus spp. in their intestinal microbiota, and may pose public health risk due to not only transmission of these resistant bacteria to humans but also contamination of the environment. The current status of antimicrobial resistance in different animal species should be continuosly monitored and control measures should also be taken.